Efficient Quantum Algorithms for GHZ and W States, and Implementation on the IBM Quantum Computer (Adv. Quantum Technol. 5‐6/2019). Issue 5 (12th June 2019) - Cruz, Diogo; Fournier, Romain; Gremion, Fabien; Jeannerot, Alix; Komagata, Kenichi; Tosic, Tara; Thiesbrummel, Jarla; Chan, Chun Lam; Macris, Nicolas; Dupertuis, Marc‐André; Javerzac‐Galy, Clément
Abstract : Entanglement is a fundamental resource in quantum information and technology. In article number1900015, Clément Javerzac‐Galy and co‐workers investigate efficient new algorithms to create N ‐qubit Greenberger–Horne–Zeilinger (GHZ) and W states with time‐complexity scaling linearly and logarithmically in N . Quantum circuits are implemented on the IBM quantum computer up to N = 16, and entanglement is investigated through tomography (and other methods) as shown in the cover picture. While the fidelity decreases with increasing N, it does so more slowly for the logarithmic algorithms. (Image design by Chun Lam Chan.)